Parallel magnetotransport in multiple quantum well structures: Низкоразмерные и сверхпроводящие системы - Sheregii, E.M.; Jasik, A.; Strupiński, W.; Mleczko, K.; Stadler, A.; Kolek, A.; Tomaka, G.; Marchewka, M.; Ploch, D.; Jakiela, R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The results of investigations of parallel magnetotransport in AlGaAs/GaAs and InGaAs/InAlAs/InP multiple quantum wells structures (MQW`s) are presented in this paper.The MQW`s were obtained by metalorganic vapour phase epitaxy with different shapes of QW, numbers of QW and levels of doping. The magnetotransport measurements were performed in wide region of temperatures (0.5–300 K) and at high magnetic fields up to 30 T (B is perpendicular and current is parallel to the plane of the QW). Three types of observed effects are analyzed: quantum Hall effect and Shubnikov—de Haas oscillations at low temperatures (0.5–6 K) as well asmagnetophonon resonance at higher temperatures (77–300 K).